Vision-based autonomous tracking and landing of a fully-actuated rotorcraft. (August 2019) - Bhargavapuri, Mahathi; Shastry, Animesh Kumar; Sinha, Harsh; Sahoo, Soumya Ranjan; Kothari, Mangal
Abstract: Autonomous landing is a challenging phase of flight for an aerial vehicle, especially when attempting to land on a moving target. This paper presents vision-based tracking and landing of a fully-actuated tilt-augmented quadrotor on a moving target. A fully-actuated vehicle allows higher freedom in terms of control design and a larger flight envelope since the position and attitude states are decoupled. An adaptive control law is designed to track a moving target with only relative position information from a camera. Low-cost hardware is used, and experiments are carried out to validate the proposed methodology for targets moving at realistic speeds.